2018
DOI: 10.1021/acsami.8b12663
|View full text |Cite
|
Sign up to set email alerts
|

Parylene-Based Double-Layer Gate Dielectrics for Organic Field-Effect Transistors

Abstract: We demonstrate high-performance and stable organic field-effect transistors (OFETs) using parylene-based double-layer gate dielectrics (DLGDs). DLGDs, consisting of parylene C as the upper layer and F as the lower layer, are designed to simultaneously provide good interface and bulk gate dielectric properties by exploiting the advantages of each gate dielectric. The structural effects of DLGDs are systematically investigated by evaluating the electrical characteristics and dielectric properties while varying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…As for the defect states at dielectric interfaces, generally these could be reduced by passivation of the SiO 2 surface with self-assembled monolayers (SAMs) or polymer dielectric. However, SAMs and polymer dielectric themselves also suffer from chemical and physical instability, which may create new surface states for charge trapping. It was found that the charge-trapping activation energy of long-chain-length-SAM-treated SiO 2 was much lower than that of untreated SiO 2 , indicating the easy formation of charge traps and the worse bias-stress instability of device. , On the other hand, the polar groups of SAMs and polymer dielectric can induce additional charge traps with different energy levels, leading to undesirable instability and performance degradation of OFETs. , As defect states cannot be completely removed, bias-stress instability is a ubiquitous issue of OFETs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the defect states at dielectric interfaces, generally these could be reduced by passivation of the SiO 2 surface with self-assembled monolayers (SAMs) or polymer dielectric. However, SAMs and polymer dielectric themselves also suffer from chemical and physical instability, which may create new surface states for charge trapping. It was found that the charge-trapping activation energy of long-chain-length-SAM-treated SiO 2 was much lower than that of untreated SiO 2 , indicating the easy formation of charge traps and the worse bias-stress instability of device. , On the other hand, the polar groups of SAMs and polymer dielectric can induce additional charge traps with different energy levels, leading to undesirable instability and performance degradation of OFETs. , As defect states cannot be completely removed, bias-stress instability is a ubiquitous issue of OFETs.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 On the other hand, the polar groups of SAMs and polymer dielectric can induce additional charge traps with different energy levels, leading to undesirable instability and performance degradation of OFETs. 22,23 As defect states cannot be completely removed, bias-stress instability is a ubiquitous issue of OFETs. Beyond reducing defect states, suppressing charge trapping plays a more significant role in improving the bias-stress stability of OFETs.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that the bilayer cases exhibited similar morphological results to those of the single case of the GI layer on top. Therefore, both FCOC+FPVDF and AGPTi+FPVDF exhibited superior μ FET values compared to those of the single FPVDF-HFP layer, as the field/charge at the interface was increased due to the presence of a high- k underlying layer, while maintaining large crystals favorable for charge transport …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both FCOC+FPVDF and AGPTi+FPVDF exhibited superior μ FET values compared to those of the single FPVDF-HFP layer, as the field/charge at the interface was increased due to the presence of a high-k underlying layer, while maintaining large crystals favorable for charge transport. 41 Through similar analyses, the cases of PTCDI-C13 devices were identified. Layered pancake-shaped crystalline structures were observed in the PTCDI-C13 layers deposited on the printed GI films (Figure S3b).…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of lightweight, energy-saving and low-cost light sources, organic luminescent materials are of latent applied value for organic laser dyes, 1,2 fluorescent probes for bioimaging, 3,4 fluorescent sensors for metal ions, 5,6 organic field effect transistors (OFETs), 7,8 organic photovoltaic cells (OPVs) 9,10 and organic light-emitting diodes (OLEDs) [11][12][13] owing to their stable, colorful and emissive characteristics. Besides, they could possess attractive X-ray-excited luminescence characteristics (such as a tailored color gamut and high quantum yields) and definitely offer emerging uses for flexible X-ray imaging with low cost, large volume and fast response time.…”
Section: Introductionmentioning
confidence: 99%